Assessing the conservation value of medicinal plant collections in Bogor Botanic Gardens, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hidayat S, Zuhud EAM, Widyatmoko D, Bahruni. 2021. Assessing the conservation value of medicinal plant collections in Bogor Botanic Gardens, Indonesia. Biodiversitas 22: 696-706.  Botanic gardens contain plant collections for the purpose primarily for ex-situ conservation, yet the public rarely appreciates these collections. As such, assessing the conservation value of botanic gardens collections is very important as an effort to increase public awareness of the importance of botanic gardens and their plant collections. This research aimed to assess the conservation value of plant collection in Bogor Botanic Gardens (BBG), Indonesia using quantitative and qualitative methods. We focused our assessment on medicinal plant collections with the habitus of tree. Conservation value of a plant collection was approached by preservation value and utilization value both quantitatively using monetary units and qualitatively using non-monetary index. Based on these two approaches, quantitatively most (91%) of the medicinal plant collections in BBG assessed in this study have a value of more than one million rupiahs, even 21% have a value of more than 100 million rupiahs, implying the high monetary value of medicinal plant collection in Bogor Botanic Gardens. Meanwhile, qualitatively, the conservation value score of a species will be strongly influenced by the existence of protection laws issued by the government and the cultural level of plants' use by the community. Our framework of assessing the conservation value of plant collections, especially those with medicinal purposes, can be replicated in other botanic gardens.
Keywords: Conservation value, quantitative, qualitative